2021
DOI: 10.1007/s00208-021-02157-y
|View full text |Cite
|
Sign up to set email alerts
|

Khovanov homotopy type, periodic links and localizations

Abstract: Given an m-periodic link $$L\subset S^3$$ L ⊂ S 3 , we show that the Khovanov spectrum $$\mathcal {X}_L$$ X L constructed by Lipshitz and Sarkar admits a group action. We relate the Borel cohomology of $$\mathcal {X}_L$$ X … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…The main work is to compute the E ∞ -page of the spectral sequence (Item (Θ-3)); the other properties are immediate. The strategy is similar to Stoffregen-Zhang's [SZ] and Borodzik-Politarczyk-Silvero's [BPS21]: we prove that the fixed points of the Z/2-action induced by the strong inversion on a CW complex representing the Khovanov stable homotopy type of K is related to the annular Khovanov stable homotopy type of (K 1 , K 0 ), and then apply classical Smith theory.…”
Section: The Localization Theorem For Strongly Invertible Knotsmentioning
confidence: 71%
See 1 more Smart Citation
“…The main work is to compute the E ∞ -page of the spectral sequence (Item (Θ-3)); the other properties are immediate. The strategy is similar to Stoffregen-Zhang's [SZ] and Borodzik-Politarczyk-Silvero's [BPS21]: we prove that the fixed points of the Z/2-action induced by the strong inversion on a CW complex representing the Khovanov stable homotopy type of K is related to the annular Khovanov stable homotopy type of (K 1 , K 0 ), and then apply classical Smith theory.…”
Section: The Localization Theorem For Strongly Invertible Knotsmentioning
confidence: 71%
“…Similar results have been proved before, for other kinds of symmetries. Stoffregen-Zhang [SZ] and Borodzik-Politarczyk-Silvero [BPS21] showed that there is a spectral sequence relating the Khovanov homology of a periodic knot (a knot preserved by rotation around an axis disjoint from it) and the annular Khovanov homology of its quotient (see also [Cor,Zha18]). An analogous result relating the symplectic Khovanov homology of a 2-periodic knot and of its quotient was proved earlier by Seidel-Smith [SS10].…”
Section: Introductionmentioning
confidence: 99%
“…The proof of the first statement uses Kronheimer and Mrowka's spectral sequence, the second uses Dowlin's spectral sequence, and the third uses an annular version of Kronheimer and Mrowka's spectral sequence [179,181], Dowlin's spectral sequence, the spectral sequences for periodic knots [26,167] mentioned above, further hard results on Floer homology [37,97,102,179,181] and the sl 2 (C)-action on annular Khovanov homology [57].…”
Section: Signs and Spectral Sequencesmentioning
confidence: 99%
“…We emphasize some differences and similarities between this paper and others appearing in the literature. There is no group action on the links considered in this paper, so our box maps and homotopy coherent refinements are different from those in [6,21,24]. Functors 2 n → B Z/2Z are considered in [23], and there the authors introduce actions of Z/2Z and Z/2Z × Z/2Z, which act internally on each box.…”
Section: From Burnside Functors To Stable Homotopy Typesmentioning
confidence: 99%
“…It is important to note that no group action is assumed to be present on the link L ⊂ A×I, so the context for our work is different from that in [6,21,24]. Therefore X r Aq (L) may be thought of as an "equivariant refinement" of X A (L), a structure that is not apparent in other constructions of the annular spectrum X A (L).…”
Section: Introductionmentioning
confidence: 99%